Masa Depan Auditing di Tengah Revolusi AI dan Blockchain: Peluang, Kendala, dan Agenda Riset Strategis - Sasha Salsabilah; Rina Tjandrakirana DP (GLOBAL SCIENTS PUBLISHER, 2026)
The revolution of Artificial Intelligence (AI) and Blockchain has triggered a fundamental transformation in the auditing profession. This research aims to map current literature regarding the integration of these two technologies to identify opportunities, constraints, and strategic research agendas for the future. Employing a systematic literature review of 31 scientific articles from 2020-2026, this study finds that the synergy between AI and Blockchain offers significant opportunities to enhance audit quality through real-time monitoring, automation of procedures, and strengthening the integrity of digital evidence. However, implementation faces substantial hurdles, including high infrastructure costs, emerging cybersecurity risks, and ethical challenges concerning algorithmic transparency. Through the lens of Signaling Theory and Legitimacy Theory, this research explains how the adoption of advanced technology functions as a positive signal of financial information quality and a firm's effort to maintain operational legitimacy in the eyes of stakeholders within the digital ecosystem. These findings formulate a strategic research agenda focusing on developing ethical AI governance frameworks and standardized blockchain-based auditing. This study provides theoretical and practical contributions for regulators and practitioners in navigating the transition toward an integrated digital audit era.